2021
DOI: 10.1002/aocs.12562
|View full text |Cite
|
Sign up to set email alerts
|

Increased oilseed shelf life using peanut flour biopackages

Abstract: This study analyzed the ability of defatted peanut flour packaging to preserve chemical quality stability of sunflower seeds throughout storage. Sunflower seed samples packaged in defatted peanut flour pouches (RS‐DPFP), high‐barrier plastic pouches made of ethylene vinyl alcohol (RS‐EVOH) and plastic pouches made of polyethylene (RS‐PE) were stored for 30 days at room temperature. Peroxide values and conjugated dienes showed a lower increase in RS‐DPFP and RS‐EVOH than in RS‐PE samples during storage. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 35 publications
4
11
0
Order By: Relevance
“…Similar results were observed in the research carried out by Riveros et al. (2021), who also detected arachidic acid (20:0), eicosenoic acid (20:1), and behenic acid (22:0) in sunflower seeds, but in residual proportions. It was observed that during storage time, changes in the fatty acid composition of the seeds occur; mainly in the percentage of linoleic acid, which was considerably reduced in all samples, but mainly in the SF‐C samples.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Similar results were observed in the research carried out by Riveros et al. (2021), who also detected arachidic acid (20:0), eicosenoic acid (20:1), and behenic acid (22:0) in sunflower seeds, but in residual proportions. It was observed that during storage time, changes in the fatty acid composition of the seeds occur; mainly in the percentage of linoleic acid, which was considerably reduced in all samples, but mainly in the SF‐C samples.…”
Section: Resultssupporting
confidence: 91%
“…The main volatile compounds identified in the sunflower treatments, on the first and last days of storage, are shown in Table 2. It is known that alkanes derive from the thermal degradation of long‐chain fatty acids by autoxidation or homolysis (Mottram, 2017), and hexanal, 2‐octenal, (E), and 2,4‐decadienal are compounds derived specifically from the autoxidation of linoleic acid (Riveros et al., 2021). For its part, nonanal could derive from the decomposition of oleic acid hydroperoxide (Fu et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sunflower seeds have high lipid content (55%-60%), mainly formed by unsaturated fatty acids such as oleic (14%-39%) and linoleic acid (48%-74%), making them susceptible to oxidative deterioration (Khan et al, 2015). Although there are some shelf-life studies correlating off-flavors and off-odors with lipid oxidation indicators and consumer acceptance of oil-rich foods (Camiletti et al, 2023;Grosso et al, 2017Grosso et al, , 2020Martín et al, 2019), few authors have reported stability studies on sunflower seeds with edible coating and antioxidant compounds (Camiletti et al, 2023;Quiroga et al, 2013;Riveros et al, 2013Riveros et al, , 2016Riveros et al, , 2021. No work has been found on sunflower seeds with the incorporation of microencapsulated polyphenolic compounds.…”
Section: Introductionmentioning
confidence: 99%